PERFORMANCE EVALUATION OF WIRELESS SENSOR NETWORK ROUTING PROTOCOL FOR VOLCANO ACTIVITY MONITORIN - Mukti, Fransiska Sisilia; Lorenzo, Juan Enrico (LPPM Universitas Nusa Mandiri, 2022)
As a country with the most volcanoes in the world, the Indonesian government must provide accurate and up-to-date information on the activity of active volcanoes. Until 2021, only 59% of mountains were directly monitored. Monitoring volcanic activity is not an easy thing to do. Visual observation alone is not enough, and instrumental comment is needed. Wireless Sensor Network (WSN) is a new opportunity to conduct a real-time and low-cost monitoring system for volcanic activity. However, the placement of independent WSN sensors in locations that are difficult to access creates new reliability and energy consumption problems. Therefore, we need a reliable communication line design for data transmission and path determination that does not drain sensor energy. This study specifically evaluates the performance of several routing protocols on WSN (proactive, reactive, and hybrid) to provide recommendations for the best routing design for volcanic activity monitoring needs. The simulation results of 6 WSN routing protocols using the NS-2 simulator show that the proactive protocol provides the smallest delay value, and the reactive protocol shows the highest data transmission success ratio but with the best residual energy. In contrast, the hybrid protocol could maintain a stable throughput value during data transmission.